The Influence of Developing an Understanding of Basic Programming Concepts Through Educational Games as A Learning Method For Elementary School Students. - Kurnianti, Apriliya; Praditia, Rizky Nanda; Qodri, Krisna Nuresa (Universitas Muhammadiyah Yogyakarta, 2024)
Integrating engaging learning methods into the educational landscape has become increasingly crucial for enhancing student understanding and engagement. This study investigates the impact of educational games as a learning method for improving elementary school students' comprehension of basic programming concepts. The research hypothesizes that educational games can significantly enhance the understanding of programming concepts by making abstract ideas more tangible and engaging through interactive and enjoyable learning environments. Using a quasi-experimental design, the study involved two groups of elementary school students: the experimental group, which utilized an educational game designed for teaching introductory programming concepts, and the control group, which received traditional instruction. Both groups underwent assessments of their understanding of basic programming concepts before and after the intervention through standardized tests. The results demonstrated a statistically significant improvement in the scores of students in the experimental group compared to those in the control group. This suggests that educational games not only aid in better understanding complex subjects such as programming and increase students' motivation and engagement levels. The findings of this study contribute to educational practices by illustrating how educational games can effectively support the introduction and teaching of programming at an early age within the elementary educational system. Furthermore, the study highlights the potential of integrating such tools into standard curricula to enhance student learning across various subjects. The study urges future research to explore the long-term impacts of educational games on learning outcomes and how these tools can be further integrated into the educational system